Synthesis, Characterization and Application of 1-Butyl-3 Methylimidazolium Chloride as Green Material for Extractive Desulfurization of Liquid Fuel - Swapnil A. Dharaskar; Mahesh N. Varma; Diwakar Z. Shende; Chang Kyoo Yoo; Kailas L. Wasewar (The Scientific World Journal)
The possible application of imidazolium ionic liquids as energy-efficient green material for extractive deep desulfurization of liquid fuel has been investigated. 1-Butyl-3-methylimidazolium chloride [BMIM]Cl was synthesized by nucleophilic substitution reaction of n-methylimidazolium and 1-chlorobutane. Molecular structures of the ILs were confirmed by FTIR, 1H-NMR, and 13C-NMR. The thermal properties, conductivity, solubility, water content and viscosity analysis of [BMIM]Cl were carried out. The effects of reaction time, reaction temperature, sulfur compounds, and recycling of IL without regeneration on dibenzothiophene removal of liquid fuel were presented. In the extractive desulfurization process, the removal of dibenzothiophene in n-dodecane using [BMIM]Cl was 81% with mass ratio of 1 : 1, in 30 min at 30°C under the mild reaction conditions. Also, desulfurization of real fuels with IL and multistage extraction were studied. The results of this work might offer significant insights in the perceptive use of imidazoled ILs as energy-efficient green material for extractive deep desulfurization of liquid fuels as it can be reused without regeneration with considerable extraction efficiency.